Technique of analysis and description of artistic radio genres - Bachura-Wojtasik, Joanna; Sygizman, Kinga (Methods of communication and media researches. Theoretical and analytical perspective, 2021)
The chapter discusses a research technique that allows to define in narrative audio forms the relationship between "truth" and "fabrication", the style of the pieces, the rhetoric of editing, and the composition of the audio works. It presents the division - the determinant of which has been editing – that take into account the creative processing of facts and the use of content of different origin and status in a radio documentary and radio play.